Telaah Atas Fenomena Mimetika Kekerasan di Ruang Maya dalam Terang Pemikiran René Girard - Ardhana, Nicolaus Yudi (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2020)
Internet and cyberspace are now loaded with various forms of violent material. Violence tends to be contagious and could be easily imitated by someone, since humans are naturally mimetic creatures. This situation may create serious problems such as desensitization, mimetics of violence, banality of violence, and justification of the acts of violence. Violence is continuously replicated and imitated both in the cyberspace and in the day-to-day reality. Even now violence is rapidly widespread in various forms and is increasingly difficult to contain. René Girard, with his theory of mimetics, tries to dismantle the mimetic mechanism that has been rooted in the acts of violence. Religion, culture, education, and the state seem not able to provide alternative ways to respond to this situation. By way of exploring Girard’s critical ideas, this article attempts to offer some alternatives to respond to the situation of violence in the cyberspace and the internet. The mimetic spiral of violence could be terminated when humans become more critical and creative as “positive imitators”.